Critical Review of Biotransformational Studies on Steroids by Using Culture of Cunninghamella blakesleeana - Azizuddin; Iqbal, M.; Musharraf, Syed G. (Letters in Organic Chemistry, 2021)
For several decades, biotransformational studies on steroidal compounds have gained a lot of attention because it is an efficient approach for the structural modification of complicated natural or synthetic compounds with high regio-, chemo- and stereoselectivity at environmentally friendly conditions. This review summarizes the use of different strains of Cunninghamella blakesleeana for the biotransformation of sixteen steroids 1-16 into a variety of transformed products. The transformed products may be important as a drug or precursor for the production of important pharmaceuticals. The types of reactions performed by C. blakesleeana include hydroxylation, epoxidation, reduction, demethylation, oxidation, glycosidation, double bond formation, side-chain degradation, isomerisation and opening of an isoxazol ring, which would be difficult to produce by traditional synthesis.
Keywords: steroids